Resurgence of respiratory syncytial virus with dominance of RSV-B during the 2022–2023 season - Korsun, Neli; Trifonova, Ivelina; Madzharova, Iveta; Alexiev, Ivaylo; Uzunova, Iordanka; Ivanov, Ivan; Velikov, Petar; Tcherveniakova, Tatiana; Christova, Iva (Frontiers in Microbiology, 2024)
Background Respiratory syncytial virus (RSV) is a common cause of upper and lower respiratory tract infections. This study aimed to explore the prevalence of respiratory syncytial virus (RSV) and other respiratory viruses in Bulgaria, characterize the genetic diversity of RSV strains, and perform amino acid sequence analyses of RSV surface and internal proteins. Methods Clinical and epidemiological data and nasopharyngeal swabs were prospectively collected from patients with acute respiratory infections between October 2020 and May 2023. Real-time PCR for 13 respiratory viruses, whole-genome sequencing, phylogenetic, and amino acid analyses were performed. Results This study included three epidemic seasons (2020–2021, 2021–2022, and 2022–2023) from week 40 of the previous year to week 20 of the following year. Of the 3,047 patients examined, 1,813 (59.5%) tested positive for at least one viral respiratory pathogen. RSV was the second most detected virus (10.9%) after SARS-CoV-2 (22%). Coinfections between RSV and other respiratory viruses were detected in 68 cases, including 14 with SARS-CoV-2. After two seasons of low circulation, RSV activity increased significantly during the 2022–2023 season. The detection rates of RSV were 3.2, 6.6, and 13.7% in the first, second, and third seasons, respectively. RSV was the most common virus found in children under 5 years old with bronchiolitis (40%) and pneumonia (24.5%). RSV-B drove the 2022–2023 epidemic. Phylogenetic analysis indicated that the sequenced RSV-B strains belonged to the GB5.0.5a and GB5.0.6a genotypes. Amino acid substitutions in the surface and internal proteins, including the F protein antigenic sites were identified compared to the BA prototype strain. Conclusion This study revealed a strong resurgence of RSV in the autumn of 2022 after the lifting of anti-COVID-19 measures, the leading role of RSV as a causative agent of serious respiratory illnesses in early childhood, and relatively low genetic diversity in circulating RSV strains.